3(y-2x) = 5(y-2x)-8

-1/3(x-5y)=(y-x)-4

### 1 Answer | Add Yours

Distribute first and second equation:

`3y - 6x = 5y - 10x - 8`

`-1/3x + 5/3y = y - x - 4` Multiply by 3 to get rid of denominators.

`-x + 5y = 3y - 3x - 12`

Rewrite both h equations in standard form: `ax + by = c`

`4x -2y = -8`

`2x +2y = -12` Divide both equations by 2.

`2x - y = -4`

`x + y = -6` Add the 2 equations together to solve for x.

`3x = -10` Divide by 3.

`x = -10/3` Substitute in equation to solve for y.

`-10/3 + y = -6`

`y = -8/3`

Solution: `(-10/3, -8/3)`

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes